2009
DOI: 10.1007/s00216-009-2952-0
|View full text |Cite
|
Sign up to set email alerts
|

Depolymerization study of sodium hyaluronate by flow field-flow fractionation/multiangle light scattering

Abstract: Thermal depolymerization of ultrahigh-molecular-weight (UHMW) sodium hyaluronate (NaHA) was studied systematically by using frit-inlet asymmetrical flow field-flow fractionation/multiangle light scattering/differential refractive index (FI-AFlFFF/MALS/DRI). FI-AFlFFF was utilized for the size separation of NaHA samples which had been thermally degraded for varied treatment times, followed by light-scattering detection to determine MW and structural information of degraded NaHA products. Analysis of NaHA produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Figure 11A shows the fractograms of the four samples (control and samples treated thermally for 10, 20, and 30 min) including both the LS and DRI signals [37]. In the figure, F3 and F4 (marked with slashes) are the time intervals for two collected fractions that will be explained later Time (min) Figure 9.…”
Section: Effect Of Thermal Treatmentmentioning
confidence: 98%
See 1 more Smart Citation
“…Figure 11A shows the fractograms of the four samples (control and samples treated thermally for 10, 20, and 30 min) including both the LS and DRI signals [37]. In the figure, F3 and F4 (marked with slashes) are the time intervals for two collected fractions that will be explained later Time (min) Figure 9.…”
Section: Effect Of Thermal Treatmentmentioning
confidence: 98%
“…Thermal treatment is performed by heating the raw material (10 mg/mL in 0.3 M NaCl solution) at 100°C for 5–30 min in 5 min intervals, and the resulting solutions are diluted with 0.1 M NaNO 3 to 0.8–1.0 mg/mL and left overnight without stirring at 4°C. Figure 11A shows the fractograms of the four samples (control and samples treated thermally for 10, 20, and 30 min) including both the LS and DRI signals 37. In the figure, F3 and F4 (marked with slashes) are the time intervals for two collected fractions that will be explained later.…”
Section: Characterization Of Naha By Flfff‐mals‐drimentioning
confidence: 99%
“…It has been shown that, in practice, FlFFF gives better resolution for MW higher than about 10 5 43. FlFFF has shown its applicability for separation of HA or HA‐like molecules 44–50, for which the frit‐inlet FlFFF, another variant of FlFFF, was mostly used.…”
Section: Introductionmentioning
confidence: 99%
“…A series of papers have been published in which AsFlFFFF-MALS was applied to study the degradation of ultrahighmolecular weight hyaluronate under the influence of thermal stress [90], ultrasonic, enzymatic or pH [91]. Electron irradiation effect was applied to study scleroglucan degradation, because of its resistance to hydrolysis, temperature and electrolytes [92], and via AsFlFFF the presence of low and high molar mass fractions could be proved.…”
Section: Polysaccharidesmentioning
confidence: 99%